Speed bumps ahead for electric-vehicle charging. - Fairley, P. (IEEE spectrum)
As major automakers like Nissan, Mitsubishi, General Motors, and others are preparing plug-in hybrid electric cars, electric utilities are both salivating at the business opportunity and quietly fretting over potential outages that could mar the electric-vehicle rollout. Thousands of EVs use the power grid for charging at night, using otherwise idle generating plants because of this power grids are breaking down. Utilities worry that EV charging could black out the neighborhoods of some early EV adopters and give the emerging technology a black eye. Policy experts worry that the change in the grid's use could unintentionally muck up their green energy plans.